Pengaruh Motivasi, Budaya Organisasi, Produktivitas Dalam Peningkatan Kinerja Pegawai Di UPTD PJU - Esse, Andi (Movere Journal, 2025)
This research aims to determine the impact of Work Motivation, Organizational Culture, and Work Productivity on the performance of employees at UPTD PJU in Parepare City. This is a quantitative study with the subjects being the employees at the UPTD PJU office in Parepare City. The sampling in this study uses the census sampling technique, where all members of the population are used as samples, involving a total of 96 employees as research samples. Data collection was conducted using a questionnaire, which was then analyzed using path analysis. The results of this study indicate that in the first path or sub-structural model, Work Motivation, Organizational Culture, and Productivity have a significant effect on Performance both simultaneously and partially. The results of the second path or sub-structural model also show that Work Motivation, Organizational Culture, and Productivity have a significant effect on Work Performance both simultaneously and partially.